Mental Health and its Relationship With Social Determinants Of Health Among Immigrant Populations - Ravi Kumar Singh; Siti Nur Aminah; Jason Lee Kwang (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This article explores the relationship between mental health outcomes and social determinants of health among immigrant populations. By analyzing survey data, the research identifies key factors such as socioeconomic status, access to healthcare, and social support that influence mental health. The findings suggest that addressing social determinants is essential for improving mental health outcomes and providing effective support services for immigrants.